Quality of service for video packet over peer to peer network using active measurement - Joni, Muhammad Affan (2008)
The purpose of this project is to see the performance of Peer-to-Peer (P2P) network in Gnutella system. P2P are self-organizing networks that aggregate large amount of heterogonous computers called nodes or peers. In P2P systems, peers can communicate directly with each other for the sharing and exchanging of data, besides the data exchange these peer nodes also share their communication and storage resources. One of the P2P mostly used is Gnutella. Gnutella is feasibly and still firmly established as the third-largest peer-to-peer network. This project will observe the problem of real-time streaming of video packet over Gnutella system from a single sender to a single receiver. This project concentrate on the development of an optimum model using Gnutella system as well as evaluating of the quality adaptation of the streaming mechanism. The simulation process was done using NS2 with 3 scenarios, which are using bandwith 512 kbps, 256 kbps, and 128 kbps. The simulation result shows that to achieve the good quality of sending video packet is using bigger bandwith. It is also shows that delay time will increase when the traffic is full. In order to achieve the right bandwith to send the video packet over the Gnutella system, it is depend on the frame rate, quantization and the resolution of the video packet.